The insurance underwriting cycle: Does it vary by insurers? - Nge Nge, Chaw Su (2011)
This paper examines the factors causing the underwriting cycle. An empirical analysis is done for 4 groups, for European and the three biggest insurance markets in Europe; United Kingdom, Germany and France. By comparing the underwriting cycle based on countries, it can be seen if local market characteristics affect the nature of the cycle. In addition, by using the empirical results I have tried to analyse if the Cummins and Outreville model or the Capacity Constraint theory holds.